Household Debt Vulnerability and Directions for Risk Management - Young Il Kim (Korea Development Institute (KDI), 2015)
Korea's households and banks seem relatively sound in terms of their loss-absorbing capacities. However, a number of worrying signs are present. Some of the negative indicators are the rising share of non-bank consumer loans; the large share of real estate out of household assets, borrowing in the form of short-term balloon payment loans, and the credit risk of low-income indebted households. Against this backdrop, a sound and effective risk management system needs to be designed based on a proper assessment of the current situation while differentiating normal from emergency measures and ex ante from ex post measures. - The recent debate over household debt has included some mixed discussions in terms of risks to financial and social stability, micro-level conditions, and macro-level effects. - The credit risk of households with loans from (systemically important) banks appears limited, while the risk of households with non-bank borrowings is relatively high. - The majority of debt can be found in households whose repayment ability is relatively strong in terms of the level of income and (net) asset. - The characteristics of asset and liability composition of household balance sheets have raised concerns about a liquidity mismatch between assets and liabilities and the risk of debt deflation. - The large increase in household credit activity has led to a rise in the number of people in default, suggesting a need for a firm establishment of lending practices of financial institutions based on repayment abilities and an improvement in consumer debt-relief programs. - Major tasks that lie ahead include a moderate degree of debt-deleveraging and mitigation of its downward pressure, stabilizing the loan structure, reconfiguring the consumer debt-relief programs, redefining the role of credit policies from the areas of social safety net, and improving labor market conditions and household income. - Suitable responses should be chosen and implemented for different situations based on objective assessment and understanding on the given situations. - Approaches for risk management should be designed in a way that differentiates between normal and emergency measures and between ex ante and ex post measures. - Attention should be paid to the vulnerability of low-income borrowers though their credit risk may not pose systemic risks to the economy.
Keywords: 330